Literatur Review: Acupressure Pericardium (P6) Therapy to Reduce the Frequency of Nausea and Vomiting in Pregnant Woman - Yuliana, Ana; Sulistiyanti, Anik; Ifalahma, Darah (Proceedings of the International Conference on Nursing and Health Sciences, 2024)
Nausea and vomiting are physiological. This physiological condition will turn into pathology if good treatment is not carried out. One non-pharmacological treatment to reduce nausea and vomiting can be acupressure. Nausea, vomiting is often considered a normal thing that occurs in pregnant women, so it is often ignored. Symptoms of nausea can be severe if not managed properly. Various efforts have been made to reduce maternal nausea and vomiting. In addition to pharmacological therapy can also be carried out nonphamacological therapy that is simple, inexpensive, effective, and without adverse side effects, namely in the form of acupressure or massage at the point 6 of the pericardium. The purpose of the study was to measure literature related to pericardium acupressure. The method used in this study is metadata analysis using a literature review by searching for relevant articles. The review source uses electronic media from several databases including Science Direct and Google Scholar which were published from 2015 to 2020. With the keywords, vomiting/vomiting; nausea/nausea; pregnancy/pregnant women; acupressure/acupressure; pericardium 6/ neiguan. Results: Based on the results of a literature review of several studies, it shows that there is an effect of providing acupressure techniques on reducing nausea and vomiting in pregnant women in the first trimester. Discussion: Acupressure at pericardium point 6 can produce good evaluations in mothers who experience nausea and vomiting in the mild and moderate categories. Acupressure therapy also does not require taking drugs because with acupressure therapy the body already contains drugs. Conclusion: The use of the pericardium 6 acupressure method in pregnant women in reducing nausea and vomiting shows its effectiveness.